Opening up animal research and science-society relations?: a thematic analysis of transparency discourses in the United Kingdom - McLeod, Carmen; Hobson-West, Pru (Sage, 2016)
The use of animals in scientific research represents an interesting case to consider in the context of the contemporary preoccupation with transparency and openness in science and governance. In the United Kingdom, organisations critical of animal research have long called for more openness. More recently, organisations involved in animal research also seem to be embracing transparency discourses. This article provides a detailed analysis of publically available documents from animal protection groups, the animal research community and government/research funders. Our aim is to explore the similarities and differences in the way transparency is constructed and to identify what more openness is expected to achieve. In contrast to the existing literature, we conclude that the slipperiness of transparency discourses may ultimately have transformative implications for the relationship between science and society and that contemporary openness initiatives might be sowing the seeds for change to the status quo.